Influencia de la concentración del espárrago verde en bioceldas galvánicas para generar energía eléctrica - Vásquez García, Ruth Julyssa (2017)
In this research work, it analyzes the influence of asparagus concentration, variation of tungsten phosphoric acid and hydrogen peroxide, in the generation of electric energy from green asparagus residues using electrochemical biocellers. The voltage produced is measured in millivolts with a digital multitester. The results show that if the concentration of asparagus is increasing, the electrical energy produced increases exponentially in the first few hours (250mV) and later decreases progressively in time (97mV). The tungsten phosphoric acid accelerates the reaction increasing the energy produced by more than 600%. The increase in the addition of hydrogen peroxide is not very significant in the production of energy up to 500 hours of reaction, after 600 hours the differences are observed. It proves that it is possible to generate directly electrical energy by degradation of asparagus residues from the oxidation-reduction reactions in biocells